Childhood reading in the context of modern media space - Nurgaly, К.Р.; Beisenova, Ж.С.; Nurgaly, Р.Р. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
Modern tasks and functions of children's reading have determined their interrelations with the sphere of media space for children as an important part of the cultural sphere of society's life, including children's movement. The purpose of this study is to actualize children's reading in the sphere of media space as an important modern resource in the reading process. In order to achieve this goal, the article reveals the essence of the concept of media space, presents a brief note on the history of the term, which allows us to identify the legitimacy of its use in modern scientific reading. A brief review of scientific approaches to the concept of media space is presented. The authors of this article focus on the problem of verbalization of children's reading in the sphere of media space at a certain stage of its development. In this regard, the preferences of children's and teenagers' reading in the digital era are analyzed on the basis of the established ratio of paper and digital forms of children's and teenagers' reading. In the process of researching the specifics of reading activity and preferences of modern schoolchildren, the authors undertook a theoretical and empirical study of the peculiarities of children's reading ability within the media space: questionnaire method, focus groups and individual structured interview. Quantitative and qualitative analysis of the obtained results was carried out. Students of 10-15 years old of secondary schools of Almaty and Astana participated in the pilot project.